Brill's companion to Apollonius Rhodius - Papanghelis, Theodore D.; Rengakos, Antonios. (Brill's Companions to Classical Studies., 2008)
This volume on Apollonius of Rhodes, whose Argonautica is the sole full-length epic to survive from the Hellenistic period, comprises articles by eighteen leading scholars from Europe and America. Their contributions cover a wide range of issues from the history of the text and the problems of the poet's biography through questions of style, literary technique and intertextual relations to the epic's literary and cultural reception. The aim of this 2nd edition is to give an up-to-date outline of the scholarly discussion in these areas and to provide a survey of recent and current trends in Apollonian studies which will be useful also to students of Hellenistic poetry in general.